Pendampingan Guru MGMP Matematika dalam Digitalisasi Pembelajaran Statistika Berbasis R dan RMarkdown - Gangga Anuraga; Silviana Maya Purwasih; Hani Brilianti Rochmanto; Zahro Dewi Anggraeny; Sekar Rini Pratiwi (JAST : Jurnal Aplikasi Sains dan Teknologi, 2025)
This community service activity was carried out in collaboration with the Nganjuk Regency Senior High School Mathematics Teacher Working Group (MGMP) to address the issues faced by teachers who still predominantly use lecture methods, are unfamiliar with modern statistical software, and do not have digital modules, reference books, and HOTS questions based on real data. The objectives of this program were to improve teachers' competence in integrating R and RMarkdown software into statistics learning, developing interactive digital modules, producing textbooks with ISBNs, and developing a bank of HOTS questions and digital LKPDs. The methods used were training and mentoring, involving 50 partner teachers. The main outputs are a digital module for teaching statistics based on the high school curriculum, a digital statistical reference book with an ISBN, and a bank of HOTS questions with 10 interactive digital worksheets. The products of this activity are superior to previous approaches because they are interactive, contextual, and easy to update. The impact of the activity can be seen from the increase in teachers' competence in using R software from 10% to 80%, the module being used by more than 50% of partner teachers, the reference book being used by more than 70% of teachers, and the HOTS questions and LKPD being used by more than 5 schools. This program has implications for further innovation opportunities in the form of developing interactive web applications and forming a digital-based community of practicing teachers for program sustainability.ABSTRAKKegiatan pengabdian kepada masyarakat ini dilaksanakan bersama MGMP Matematika SMA Kabupaten Nganjuk untuk menjawab permasalahan guru yang masih dominan menggunakan metode ceramah, belum familiar dengan perangkat lunak statistik modern, dan belum memiliki modul digital, buku referensi, serta soal HOTS berbasis data riil. Tujuan program ini adalah meningkatkan kompetensi guru dalam mengintegrasikan software R dan RMarkdown dalam pembelajaran statistika, menyusun modul digital interaktif, menghasilkan buku ajar ber-ISBN, serta mengembangkan bank soal HOTS dan LKPD digital. Metode yang digunakan adalah pelatihan, dan pendampingan, melibatkan 50 guru mitra. Karya utama yang dihasilkan adalah satu modul digital pembelajaran statistika berbasis kurikulum SMA, satu buku referensi statistika digital ber-ISBN, dan satu bank soal HOTS dengan 10 LKPD digital interaktif. Produk kegiatan ini unggul dibanding pendekatan sebelumnya karena interaktif, kontekstual, dan mudah diperbarui. Dampak kegiatan terlihat dari meningkatnya kompetensi guru dalam penggunaan perangkat lunak R dari 10% menjadi 80%, modul digunakan oleh lebih dari 50% guru mitra, buku referensi dimanfaatkan oleh lebih dari 70% guru, dan soal HOTS serta LKPD digunakan oleh lebih dari 5 sekolah. Program ini berimplikasi pada peluang inovasi lanjutan berupa pengembangan aplikasi web interaktif dan pembentukan komunitas guru praktisi berbasis digital untuk keberlanjutan program.